Puzzle Journey Into Space - Rebecca Heddle (London Usborne Publishing Ltd, 1995)
A visit to the Space Research Centre takes a strange turn when Bobbie and Joe find themselves stepping out of the flight simulator onto an alien world. This is only the beginning of a peculiar journey through the byways of space, stopping off to explore planets and their satellites, dodging meteors, and watching out for black holes. As they travel, Joe and Bobbie slowly discover that all is not well in space, and find themselves on the trail of the evil genius "Dread" Lee Sirus, pitting their wits against his as they struggle to halt his plans for universal domination. This is the second book in the series which presents facts through fiction with the added challenge of puzzles to solve that will interest young readers aged six and over. A simple adventure story will involve the reader in action while stretching their wits and starting to teach them fascinating things about space.
Keywords: Innovations And Inventions -- Innovations And Inventions; Space Exploration -- Space Exploration